2021
DOI: 10.29228/joh.51883
|View full text |Cite
|
Sign up to set email alerts
|

Covi̇d-19 Salgin Süreci̇nde Üni̇versi̇te Öğrenci̇leri̇ni̇n Fi̇zi̇ksel Akti̇vi̇te Düzeyi̇ni̇n Yaşam Kali̇tesi̇ Üzeri̇ne Etki̇si̇

Abstract: Yapılan çalışmada COVID-19 pandemisinde üniversite öğrencilerinin fiziksel aktivite düzeyleri ile yaşam kaliteleri arasındaki ilişkinin incelenmesi ve cinsiyetlere göre bu değişkenlerin karşılaştırılması amaçlanmıştır. Çalışmaya Niğde Ömer Halisdemir 1 Bu Makalenin etik kurul onayı Niğde Ömer Halisdemir Üniversitesi'nde 02.07.2021 tarihli ve 11 sayılı toplantısının 14 sayılı karar numarası ile alınmıştır.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…These areas can be affected by the periods when individuals are confined to their homes, such as the Covid-19 process. The mobility in the life of the individual and the happiness that comes with it constitute the quality of life (Burak Aktuğ et al, 2021). In this period, it has been observed that the workload of all women, whether working or doing housework, has increased and they have become a disadvantaged social group.…”
Section: Introductionmentioning
confidence: 99%
“…These areas can be affected by the periods when individuals are confined to their homes, such as the Covid-19 process. The mobility in the life of the individual and the happiness that comes with it constitute the quality of life (Burak Aktuğ et al, 2021). In this period, it has been observed that the workload of all women, whether working or doing housework, has increased and they have become a disadvantaged social group.…”
Section: Introductionmentioning
confidence: 99%